Does China's trade expansion help African development? -- an empirical estimation - (:unkn) unknown (My University, 2013)
This paper uses Comtrade panel data to assess the impacts of imports from China, in comparison with those from the United States and France, on Sub-Saharan African manufactured exports (as proxies of production erformance). It is found that Chinese impacts are significantly positive in all sectors and in general Chinese impacts are stronger than those of the United States and France. A South-South trade theoretical framework is then explored to interpret this finding: When the absorptive capability of a poorly-developed country is quite limited and (or) a sizeable substitution effect of importing intermediate goods on this country's local production is present, it is better to import from a Southern country with a superior technology than from a Northern country with a very advanced technology. Therefore, my finding has provided evidence that China's increasing trade with Africa is helpful to African economic development.
Keywords: African Research